3g+3=5(3*g)

Simple and best practice solution for 3g+3=5(3*g) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3g+3=5(3*g) equation:


Simplifying
3g + 3 = 5(3g)

Reorder the terms:
3 + 3g = 5(3g)

Remove parenthesis around (3g)
3 + 3g = 5 * 3g

Multiply 5 * 3
3 + 3g = 15g

Solving
3 + 3g = 15g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-15g' to each side of the equation.
3 + 3g + -15g = 15g + -15g

Combine like terms: 3g + -15g = -12g
3 + -12g = 15g + -15g

Combine like terms: 15g + -15g = 0
3 + -12g = 0

Add '-3' to each side of the equation.
3 + -3 + -12g = 0 + -3

Combine like terms: 3 + -3 = 0
0 + -12g = 0 + -3
-12g = 0 + -3

Combine like terms: 0 + -3 = -3
-12g = -3

Divide each side by '-12'.
g = 0.25

Simplifying
g = 0.25

See similar equations:

| -46k-19(k-8)-(4-2k)= | | -46k-19(l-8)-(4-2k)= | | 3.5x+6=12.5 | | x-9=-6x-3 | | -19(3p-115)-425+234p= | | 7(u-8)=(3u+4) | | 1+3x=x | | 90=10x+75 | | 696969= | | y+6(8-2y)-3(7+x)+9= | | p^2+3p-4=0 | | 53-(4x+3)=4(x+8)+x | | 10x-3=63 | | 4+4=y | | 9x+5y=45 | | x+x-4=0 | | w/4+5/8-2w/2=7/8-2w/4 | | x+y+2x=0 | | 3f+5=8 | | 5r-9(r-8)-20+2r= | | X-(5-3x)=7x+5 | | M^2+14m+13=0 | | 6r-9(r+8)+30+2r= | | 1.67+.67x=2.17+3.5x+.5 | | 10=x-8+8x | | 80=8x+10 | | 18x^3+39x^2+18x= | | Y=1.5x+7 | | 6x+-7-(2x)+4-5x+13= | | -5-7= | | 6x+-7-(2x)+4-5x+13=0 | | 8x-7y=14 |

Equations solver categories